Single-component heat-aging-resistant heat-conducting silica gel and preparation method thereof

By using raw materials such as octavinylsilsesquioxane and terminal epoxy silicone oil in thermally conductive silicone gel, a complex three-dimensional cross-linked network is formed, which solves the problem of insufficient heat aging resistance of thermally conductive silicone gel and achieves thermal conductivity Balance of performance and heat aging resistance.

CN119331418APending Publication Date: 2025-01-21COLLTECH DONGGUAN BONDING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411435349.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

While pursuing high thermal conductivity, existing thermally conductive silicon gels have poor thermal aging performance, resulting in rapid rise in the temperature of the silicon gel and aging accelerates, resulting in problems such as climbing hardness, decreasing flexibility, prone to cracking or brittlement.

Method used

A single-component heat-aging resistant thermal conductive silicone gel is prepared. The raw materials include an appropriate amount of octavinyl silsesquioxane to change the cross-linking point structure of part of the silicone gel and improve the thermal resistance; at the same time, end rings are added Oxygen-based silicone oil, ellagic acid and triethylamine are cross-linked and solidified during high-temperature curing to form a complex three-dimensional cross-linked network, which evenly disperses thermal stress and improves the overall heat resistance.

Benefits of technology

It achieves a balance between good thermal conductivity and excellent thermal aging resistance of thermally conductive silicone gel, avoids local damage caused by thermal stress concentration, improves the overall heat resistance and cross-linking density of the material, and blocks oxygen penetration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005084787170000051
    Figure BDA0005084787170000051
Patent Text Reader

Abstract

The invention provides a single-component heat-aging-resistant heat-conducting silica gel and a preparation method thereof. The single-component heat-aging-resistant heat-conducting silica gel is prepared from the following raw materials in parts by weight: 70 to 80 parts of vinyl-terminated silicone oil, 8 to 10 parts of hydrogen-terminated silicone oil, 0.3 to 0.5 part of octavinyl silsesquioxane, 10 to 15 parts of epoxy-terminated silicone oil, 3 to 5 parts of ellagic acid, 0.01 to 0.03 part of triethylamine, 0.5 to 3 parts of catalyst, 0.1 to 2 parts of inhibitor and 500 to 800 parts of heat-conducting filler, wherein the epoxy value of the epoxy-terminated silicone oil is 0.1 to 0.3 mol / 100g; the epoxy-terminated silicone oil is polydimethylsiloxane of which the terminal group contains an epoxy group. Octavinyl silsesquioxane is utilized to change the structure of a part of crosslinking points of silica gel, the heat resistance of the silica gel is improved, in addition, epoxy-terminated silicone oil and ellagic acid are crosslinked and cured under the catalytic action of triethylamine when the silica gel is cured at high temperature, and the heat aging resistance can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermally conductive silicone gel, and in particular relates to a single-component heat-resistant and aging-resistant thermally conductive silicone gel and a preparation method thereof. Background Art

[0002] With the development of technology, electronic components, electrical power circuit modules, large-scale integrated circuits and other fields have further achieved high performance, high reliability and miniaturization, and the working efficiency has been continuously improved. Therefore, the heat generated by each component during operation has also increased sharply. At the same time, the application environment of components has become more stringent and complex. Therefore, in order to ensure that electronic products can play an excellent comprehensive performance and maintain a good service life, they must be thermally sealed to protect them, dissipate the heat quickly, and prevent damage caused by external moisture, dust or severe vibration.

[0003] Addition-type thermally conductive silicone gel is a compliant material composed of addition-type organic silicone gel and thermally conductive filler. In addition to the excellent high and low temperature resistance, weather resistance, electrical insulation and moisture and corrosion resistance of general addition-type silicone rubber, the softness of silicone gel also gives the material a low elastic modulus and low internal stress, and has an excellent shock absorption effect. Therefore, it has gradually developed into various fields such as automobiles, electronic appliances, and aerospace. For example, the silicone gel composition disclosed in patent CN113528082B, the silicone gel including the silicone gel, the packaging structure and the semiconductor device, the application of the technical scheme of the present invention is conducive to improving the thermal conductivity of the silicone gel prepared by using the silicone gel. At the same time, the organic titanium compound and the silane coupling agent in the silicone gel composition can improve the adhesion of the obtained silicone gel through synergistic action, while promoting the reaction between the silane coupling agent and the substrate, thereby further improving the bonding performance of the silicone gel. The low stress thermally conductive silicone gel composition disclosed in patent CN106753215B includes vinyl-containing polydiorganosiloxane, functional filler, hydrogen-containing siloxane, expansion agent, and adhesion promoter, which are cross-linked and formed under the action of a catalyst. The low stress thermally conductive silicone gel composition has low stress, strong adhesion, thermal conductivity, and flame retardancy, and can protect electronic components subjected to mechanical and thermal stress.

[0004] The above thermally conductive silicone gel has excellent thermal conductivity, is easy to replace, has good fluidity, and can be used in many fields such as mobile phones, computers, LED heat dissipation, new energy vehicles, etc. However, the pursuit of high thermal conductivity of thermally conductive silicone gel also brings other disadvantages, especially heat aging resistance. Higher thermal conductivity means that more and faster heat can be transferred to the inside of the silicone gel, and the temperature of the silicone gel rises rapidly. Long-term high temperature accelerates the aging of the silicone gel, resulting in a serious increase in hardness, a decrease in flexibility, and a greater tendency to crack or become brittle.

[0005] In summary, there is an urgent need to develop a thermally conductive silicone gel that takes into account both thermal conductivity and heat aging resistance. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a single-component heat-resistant and aging-resistant thermal conductive silicone gel and a preparation method thereof. The raw materials of the thermal conductive silicone gel include an appropriate amount of octavinyl silsesquioxane, and the octavinyl silsesquioxane is used to change the structure of the cross-linking points of some silicone gels to improve the heat resistance of the silicone gel; in addition, the raw materials also include terminal epoxy silicone oil, ellagic acid, and triethylamine. When the silicone gel is cured at high temperature, the terminal epoxy silicone oil and ellagic acid are cross-linked and cured simultaneously under the catalysis of triethylamine, and interpenetrate with the cross-linked network formed by the terminal vinyl silicone oil and the hydrogen-containing silicone oil to form a complex three-dimensional cross-linked network, which can not only disperse thermal stress more evenly, avoid local damage caused by stress concentration, and improve the overall heat resistance of the material, but also has the effect of increasing the cross-linking density, blocking oxygen penetration, and further improving the heat resistance.

[0007] In order to achieve the above purpose, the following technical solutions are adopted:

[0008] A single-component heat-resistant and aging-resistant thermally conductive silicone gel comprises the following raw materials in parts by weight: 70-80 parts of vinyl-terminated silicone oil, 8-10 parts of hydrogen-terminated silicone oil, 0.3-0.5 parts of octavinyl silsesquioxane, 10-15 parts of epoxy-terminated silicone oil, 3-5 parts of ellagic acid, 0.01-0.03 parts of triethylamine, 0.5-3 parts of catalyst, 0.1-2 parts of inhibitor, and 500-800 parts of thermally conductive filler, wherein the epoxy value of the epoxy-terminated silicone oil is 0.1-0.3 mol / 100g, and the epoxy-terminated silicone oil is polydimethylsiloxane containing epoxy groups at the end groups.

[0009] The vinyl content of the vinyl-terminated silicone oil is 0.4-0.6%, and the viscosity is 200-10000 mPa·s.

[0010] The hydrogen content of the terminal hydrogenated silicone oil is 0.1-0.3% and the viscosity is 10-100 mm 2 / s.

[0011] The catalyst is a platinum catalyst, and the content of platinum metal in the platinum catalyst is 3000-5000ppm.

[0012] The inhibitor is an alkynol compound, selected from one or a combination of two or more of 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynyl-1-cyclohexanol, and 3-phenyl-1-butyn-3-ol.

[0013] The thermal conductive filler is selected from one or a combination of two or more of aluminum oxide, aluminum nitride, zinc oxide, boron nitride, ceramic powder, and aluminum powder.

[0014] Furthermore, the thermally conductive filler is a compound of aluminum oxide and aluminum nitride in a mass ratio of 5-6:4-5.

[0015] Furthermore, the aluminum oxide is a mixture of aluminum oxides with D50 of 0.4-0.6μm, 1-3μm, 3-5μm, and 40-60μm in a mass ratio of 1:3-5:3-5:1-2; the aluminum nitride is a mixture of spherical aluminum nitride with D50 of 0.5-1μm and spherical aluminum nitride with D50 of 50-80μm in a mass ratio of 3-5:1.

[0016] The present invention also provides a method for preparing the above-mentioned single-component heat-resistant and aging-resistant thermally conductive silicone gel, comprising the following steps:

[0017] Vinyl-terminated silicone oil, hydrogen-terminated silicone oil, octavinyl silsesquioxane, epoxy-terminated silicone oil, ellagic acid, inhibitor, thermal conductive filler and thixotropic agent are mixed uniformly under temperature control, a catalyst is added, and the mixture is mixed uniformly under temperature control and vacuum conditions to obtain the above-mentioned single-component heat-resistant and aging-resistant thermal conductive silicone gel.

[0018] The temperature control is to control the temperature at 20-50°C; the vacuum condition is -0.08MPa to -0.1MPa.

[0019] The curing conditions of the single-component heat-resistant and aging-resistant thermally conductive silicone gel are 100-120° C. and 15-30 minutes.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The raw materials of the heat-conductive silicone gel of the present invention include an appropriate amount of octavinyl silsesquioxane, and the octavinyl silsesquioxane is used to change the structure of the cross-linking points of part of the silicone gel to improve the heat resistance of the silicone gel; in addition, the raw materials also include terminal epoxy silicone oil, ellagic acid, and triethylamine. When the silicone gel is cured at high temperature, the terminal epoxy silicone oil and ellagic acid are cross-linked and cured simultaneously under the catalytic action of triethylamine, and interpenetrate with the cross-linking network formed by the terminal vinyl silicone oil and the hydrogen-containing silicone oil to form a complex three-dimensional cross-linking network, which can not only disperse thermal stress more evenly, avoid local damage caused by stress concentration, and improve the overall heat resistance of the material, but also has the effect of increasing the cross-linking density, blocking oxygen penetration, and further improving the heat aging resistance. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.

[0023] The vinyl-terminated silicone oil RH-Vi500E has a vinyl content of 0.42% and a viscosity of 500 mPa·s and was purchased from Ningbo Runhe High-tech Materials Technology Co., Ltd.

[0024] The hydrogen content of the end-hydrogenated silicone oil RH-H518 is 0.18% and the viscosity is 10mm 2 / s, purchased from Ningbo Runhe High-tech Materials Technology Co., Ltd.

[0025] The epoxy-terminated silicone oil was purchased from Anhui IOTA Silicone Oil Co., Ltd., with the brand name IOTA 105-1-1 and epoxy value of 0.1 mol / 100 g; the brand name IOTA 105-1-2 and epoxy value of 0.3 mol / 100 g.

[0026] Alumina with a D50 of 0.45 μm was purchased from Sumitomo Chemical Co., Ltd.; alumina with a D50 of 2 μm, 5 μm, and 50 μm were all purchased from Aluminum Corporation of China; spherical aluminum nitride with a D50 of 1 μm and spherical aluminum nitride with a D50 of 60 μm were purchased from Cramer's Reagent.

[0027] The platinum catalyst was purchased from Shenzhen Kejunchi Technology Co., Ltd., brand PT-2000, with a platinum content of 2000 ppm.

[0028] Example 1

[0029] 80 parts of vinyl-terminated silicone oil RH-Vi500E, 10 parts of hydrogen-terminated silicone oil RH-H6, 0.5 parts of octavinyl silsesquioxane, 15 parts of epoxy-terminated silicone oil IOTA 105-1-2, 5 parts of ellagic acid, 0.01 parts of triethylamine, 0.3 parts of 3-methyl-1-butyn-3-ol, and 800 parts of thermal conductive filler were mixed uniformly at 50°C, 1.5 parts of platinum catalyst PT-2000 were added, the temperature was controlled at 50°C and the mixture was mixed uniformly under a vacuum degree of -0.1MPa to obtain the above-mentioned single-component heat-resistant and aging-resistant thermal conductive silicone gel.

[0030] The thermal conductive filler is formed by mixing 600 parts of a mixture of aluminum oxide with D50 of 0.5 μm, 2 μm, 5 μm and 60 μm in a mass ratio of 1:4:4:1 and 400 parts of a mixture of spherical aluminum nitride with D50 of 1 μm and 50 μm in a mass ratio of 5:1.

[0031] Example 2

[0032] The rest is the same as Example 1, except that the epoxy-terminated silicone oil IOTA 105-1-2 is replaced by an equal mass of epoxy-terminated silicone oil IOTA 105-1-1.

[0033] Example 3

[0034] The rest is the same as Example 1, except that the amount of the epoxy-terminated silicone oil IOTA 105-1-2 is 10 parts.

[0035] Example 4

[0036] The rest is the same as Example 1, except that the amount of octavinylsilsesquioxane used is 0.3 parts.

[0037] Example 5

[0038] 70 parts of vinyl-terminated silicone oil RH-Vi500E, 10 parts of hydrogen-terminated silicone oil RH-H6, 0.5 parts of octavinyl silsesquioxane, 15 parts of epoxy-terminated silicone oil IOTA 105-1-2, 3 parts of ellagic acid, 0.01-0.03 parts of triethylamine, 0.3 parts of 3-methyl-1-butyn-3-ol, and 800 parts of thermal conductive filler were mixed uniformly at 50°C, 1.5 parts of platinum catalyst PT-2000 were added, and the mixture was mixed uniformly at 50°C-0.1MPa to obtain the above-mentioned single-component heat-resistant and aging-resistant thermal conductive silicone gel.

[0039] The thermal conductive filler is a mixture of 600g of alumina with D50 of 0.5μm, 2μm, 5μm, and 60μm in a mass ratio of 1:4:4:1 and 400g of spherical aluminum nitride with D50 of 1μm and 50μm in a mass ratio of 5:1.

[0040] Example 6

[0041] The rest is the same as Example 1, except that the amount of thermal conductive filler is 500 parts.

[0042] Comparative Example 1

[0043] The rest is the same as Example 1, except that 0.5 parts of octavinyl silsesquioxane is replaced by 40.62 parts of vinyl-terminated silicone oil equivalent to the total amount of vinyl groups.

[0044] Comparative Example 2

[0045] The rest is the same as Example 1, except that 5 parts of ellagic acid are not added.

[0046] Example 3

[0047] The rest is the same as Example 1, except that the amount of octavinylsilsesquioxane used is 0.6 parts.

[0048] Example 4

[0049] The rest is the same as Example 1, except that the amount of octavinylsilsesquioxane used is 0.2 parts.

[0050] The silicone gels prepared in the above examples and comparative examples were subjected to the following performance tests:

[0051] Oil penetration value: Cut the cured silicone gel into 3cm*1.5cm*2cm samples, weigh and record the initial mass m0 (g), put the sample into the test fixture, place a piece of oil penetration filter paper on the top and bottom, set the rated pressure to 9.8N, put it into a 100℃ blast drying oven, take it out after 14 days, weigh and record the weight as m t (g) Calculate the oil permeation value of the sample according to the following formula,

[0052] P=(m0-m t ) / (m t / ρ)

[0053] Where ρ is the sample density, g / cm 3 ; P represents the oil permeability value of the sample g / cm 3 .

[0054] Thermal conductivity: Tested in accordance with standard GB / T 10297-98.

[0055] Shore hardness: Tested using Shore 00 durometer in accordance with ASTM D 2240.

[0056] Heat aging resistance: The tensile shear strength test specimens were placed in a heat aging condition at 150°C for 1000 hours, and then the above-mentioned Shore hardness was retested.

[0057] Table 1 Performance test results

[0058]

[0059]

[0060] It can be seen from Examples 1 and 4-6 that as the amount of octavinylsilsesquioxane increases, the oil permeation value tends to increase. When the amount is 0.6 parts, there is a sharp increase in the oil permeation value. It is speculated that a large amount of terminal vinyl silicone oil did not react with the terminal hydrogen silicone oil, reaching a level where the cross-linking structure is not sufficient to limit the seepage of the terminal vinyl silicone oil.

[0061] From the heat aging resistance test of Example 1 and Comparative Examples 1-2, it can be seen that octavinyl silsesquioxane, epoxy-terminated silicone oil, ellagic acid and triethylamine have a significant synergistic effect of improving the heat aging resistance.

[0062] It can be seen from the heat aging resistance test of the embodiments and comparative examples that the thermally conductive silicone gel prepared by the present invention has both good thermal conductivity and excellent heat aging resistance.

[0063] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A single-component heat-resistant and aging-resistant thermally conductive silicone gel, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of vinyl-terminated silicone oil, 8-10 parts of hydrogen-terminated silicone oil, 0.3-0.5 parts of octavinyl silsesquioxane, 10-15 parts of epoxy-terminated silicone oil, 3-5 parts of ellagic acid, 0.01-0.03 parts of triethylamine, 0.5-3 parts of catalyst, 0.1-2 parts of inhibitor and 500-800 parts of thermal conductive filler. The epoxy value of the epoxy-terminated silicone oil is 0.1-0.3 mol / 100 g, and the epoxy-terminated silicone oil is polydimethylsiloxane containing epoxy groups at the end groups.

2. The single-component heat-resistant and aging-resistant thermally conductive silicone gel according to claim 1, characterized in that: The vinyl content of the vinyl-terminated silicone oil is 0.4-0.6%, and the viscosity is 200-10000 mPa·s.

3. The single-component heat-resistant and aging-resistant thermally conductive silicone gel according to claim 1, characterized in that: The hydrogen content of the terminal hydrogenated silicone oil is 0.1-0.3% and the viscosity is 10-100 mm 2 / s.

4. The single-component heat-resistant and aging-resistant thermally conductive silicone gel according to claim 1, characterized in that: The catalyst is a platinum catalyst, and the content of platinum metal in the platinum catalyst is 3000-5000ppm.

5. The single-component heat-resistant and aging-resistant thermally conductive silicone gel according to claim 1, characterized in that: The inhibitor is an alkynol compound, selected from one or a combination of two or more of 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynyl-1-cyclohexanol, and 3-phenyl-1-butyn-3-ol.

6. The single-component heat-resistant and aging-resistant thermally conductive silicone gel according to claim 1, characterized in that: The thermal conductive filler is selected from one or a combination of two or more of aluminum oxide, aluminum nitride, zinc oxide, boron nitride, ceramic powder, and aluminum powder.

7. The single-component heat-resistant and aging-resistant thermally conductive silicone gel according to claim 6, characterized in that: The thermal conductive filler is a compound of aluminum oxide and aluminum nitride in a mass ratio of 5-6:4-5.

8. The single-component heat-resistant and aging-resistant thermally conductive silicone gel according to claim 7, characterized in that: The aluminum oxide is a mixture of aluminum oxides with D50 of 0.4-0.6 μm, 1-3 μm, 3-5 μm, and 40-60 μm in a mass ratio of 1:3-5:3-5:1-2; the aluminum nitride is a mixture of spherical aluminum nitride with D50 of 0.5-1 μm and spherical aluminum nitride with D50 of 50-80 μm in a mass ratio of 3-5:

1.

9. The method for preparing the single-component heat-resistant and aging-resistant thermally conductive silicone gel according to any one of claims 1 to 8, characterized in that: The steps include: Vinyl-terminated silicone oil, hydrogen-terminated silicone oil, octavinyl silsesquioxane, epoxy-terminated silicone oil, ellagic acid, inhibitor, thermal conductive filler and thixotropic agent are mixed uniformly under temperature control, a catalyst is added, and the mixture is mixed uniformly under temperature control and vacuum conditions to obtain the above-mentioned single-component heat-resistant and aging-resistant thermal conductive silicone gel.

10. The method for preparing the single-component heat-resistant and aging-resistant thermally conductive silicone gel according to claim 9, characterized in that: The temperature control is to control the temperature at 20-50°C; the vacuum condition is -0.08MPa to -0.1MPa; the curing condition of the single-component heat-resistant and aging-resistant thermal conductive silicone gel is 100-120°C, 15-30min.

Citation Information

Patent Citations

  • Low-stress thermally conductive silicone gel composition

    CN106753215B

  • Silicone gel compositions, silicone gels including the same, encapsulation structures, and semiconductor devices.

    CN113528082B